Assessing influenza vaccination success to inform COVID‐19 vaccination campaign. Issue 3 (11th October 2021) - Moreland, Ashley; Gillezeau, Christina; Alpert, Naomi; Taioli, Emanuela
Abstract: Given recent downward trends in daily rates of COVID‐19 vaccinations, it is important to reassess strategies to reach those most vulnerable. The success and efficacy of vaccination campaigns for other respiratory illnesses, such as influenza, may help inform messaging around COVID‐19 vaccinations. This cross‐sectional study examines the individual‐level factors associated with, and the spatial distribution of, predictors of COVID‐19 severity, and uptake of influenza and hepatitis B (as a negative control) vaccines across NYC. Data were obtained from the 2018 Community Health Survey (CHS), including self‐reported influenza and hepatitis B vaccine uptake, diabetes, asthma, hypertension, body mass index (BMI), age, race/ethnicity, educational attainment, borough, and United Hospital Fund (UHF) neighborhood of residence. A CDC‐defined COVID‐19 severity risk score was created with variables available in the CHS, including diabetes, asthma, hypertension, BMI ≥ 30 kg/m 2, and age ≥65 years old. After adjustment, there was a significant positive association between COVID‐19 severity risk score and influenza vaccine uptake (1: ORadj = 1.49, 95% CI 1.28–1.73; 2: ORadj = 1.99; 95% CI: 1.65–2.41; 3+: ORadj = 2.89; 95% CI: 2.32–3.60, compared to 0). Hepatitis B vaccine uptake was significantly inversely associated with COVID‐19 severity risk score (1: ORadj = 0.67; 95% CI: 0.57–0.79; 2: ORadj = 0.54; 95% CI: 0.44–0.66; 3+: ORadj = 0.45; 95% CI: 0.36–0.56, compared to 0). The influenza vaccination campaign template is effective at reaching those most at risk for serious COVID‐19 and, if implemented, may help reach the most vulnerable that have not yet been vaccinated against COVID‐19.